Sociology of Work in the Digital Age: Unraveling the Subjectification of Knowledge Workers - Abigail Albert (Indus Journal of Social Sciences, 2023)
In the digital age, the sociology of work undergoes profound transformations, particularly concerning the subjectification of knowledge workers. This study explores the intricate processes through which knowledge workers construct their professional identities, negotiate power dynamics, and navigate organizational structures in contemporary digital workplaces. Drawing on a blend of sociological theories and empirical data, including interviews and surveys, this research unravels the evolving landscape of subjectification within the knowledge economy. It underscores the role of technology, organizational cultures, and individual agency in shaping the subjectivities of knowledge workers and contributes to our understanding of work in the digital era.